Analysis of the possibility of irradiation-induced coloring of topaz in the WWR-K reactor - Aitkulov, M.; Dyussambayev, D.; Akhanov, А.; Kisselyov, К.; Bugybay, Zh; Romanova, N.; Gizatulin, Sh.; Shaimerdenov, А.; Nakipov, D. (Recent Contributions to Physics, 2021)
Nowadays, radiation technologies are widely used in industry, medicine and other fields. One of the particular cases of application of such technologies is the irradiation-induced coloring of topaz. As a result of the application of this technology, colorless topaz acquires a more noble, respectively, economically advantageous color. For this, different types of radiation can be used. In the case of irradiation-induced coloring of topaz using neutrons, it is necessary to formation optimal conditions for irradiation of topaz. First of all, in the topaz irradiation zone it is necessary to formation a "hard" neutron spectrum not only for the formation of color centers, but also to reduce the residual radioactivity in the topaz. In this work, the possibility of implementing the technology of irradiation-induced coloring of topaz in the WWR-K research reactor was evaluated. For this, the energy distribution of neutrons in the central and peripheral irradiation positions of the WWR-K reactor was determined. On the basis of the obtained values, the time to reach the target neutron fluence (1018 cm-2) was estimated. The influence of the ratio of the flux of fast to thermal neutrons on the activation of natural impurities in topaz is shown. The results of trial irradiation of topazes in the WWR-K reactor without formation special conditions are presented. Ways to optimize the conditions for irradiation of topazes in the WWR-K reactor in order to improve the economic efficiency of the work were proposed.